Decreased haemoglobin levels are associated with lower muscle mass and strength in kidney transplant recipients. Issue 4 (3rd June 2022) - Vinke, Joanna Sophia J.; Wouters, Hanneke J.C.M.; Stam, Suzanne P.; Douwes, Rianne M.; Post, Adrian; Gomes‐Neto, Antonio W.; van der Klauw, Melanie M.; Berger, Stefan P.; Bakker, Stephan J.L.; ,; De Borst, Martin H.; Eisenga, Michele F.
Abstract: Background: Post‐transplant anaemia and reduced muscle mass and strength are highly prevalent in kidney transplant recipients (KTRs). Decreased haemoglobin levels, a marker of anaemia, could adversely affect muscle mass and strength through multiple mechanisms, among others, through diminished tissue oxygenation. We aimed to investigate the association between haemoglobin levels with muscle mass and strength in KTRs. Methods: We included stable KTRs from the TransplantLines Biobank and Cohort study with a functional graft ≥1 year post‐transplantation. Muscle mass was assessed using 24 h urinary creatinine excretion rate (CER) and bioelectrical impedance analysis (BIA). Muscle strength was assessed with a handgrip strength test using a dynamometer and, in a subgroup ( n = 290), with the five‐times sit‐to‐stand (FTSTS) test. We used multivariable linear and logistic regression analyses to investigate the associations of haemoglobin levels with muscle mass and strength. Results: In 871 included KTRs [median age 58 (interquartile range (IQR), 48–66)] years; 60% men; eGFR 51 ± 18 mL/min/1.73 m 2 ) who were 3.5 (1.0–10.2) years post‐transplantation, the mean serum haemoglobin level was 13.9 ± 1.8 g/dL in men and 12.8 ± 1.5 g/dL in women. Lower haemoglobin levels were independently associated with a lower CER (std. β = 0.07, P = 0.01), BIA‐derived skeletal muscle mass (std. β = 0.22, P < 0.001), handgrip strength (std. β = 0.15, P < 0.001), and worse FTSTS test scores (std. β = −0.17, P = 0.02). KTRs in the lowest age‐specific and sex‐specific quartile of haemoglobin levels had an increased risk of being in the worst age‐specific and sex‐specific quartile of CER (fully adjusted OR, 2.09; 95% CI 1.15–3.77; P = 0.02), handgrip strength (fully adjusted OR, 3.30; 95% CI 1.95–5.59; P < 0.001), and FTSTS test score (fully adjusted OR, 7.21; 95% CI 2.59–20.05; P < 0.001). Conclusions: Low haemoglobin levels are strongly associated with decreased muscle mass and strength in KTRs. Future investigation will need to investigate whether maintaining higher haemoglobin levels may improve muscle mass and strength in KTRs.